Determination of lead, cadmium and arsenic in infant formula in the Lebanese market. (May 2021) - Elaridi, Jomana; Dimassi, Hani; Al Yamani, Osama; Estephan, Maria; Hassan, Hussein F.
Abstract: Infant formula is a common source of food and nutrition for many infants and toddlers. However, the presence of contaminants, such as toxic metals, may pose increased health risks to infants. An investigation on the occurrence of the toxic metals: lead (Pb), cadmium (Cd) and arsenic (As) in baby formula marketed in Lebanon was performed. Infant formula samples were collected from 39 brands over two production dates (78 samples in total) and analyzed for the metals using inductively-coupled plasma mass spectrometry (ICP-MS). As, Pb and Cd were observed in 59%, 8% and 10% of infant formula brands, respectively. The Pb, Cd and As contamination levels were 31.0–1040 μg/kg, 38.0–476 μg/kg and 12.0–251 μg/kg, respectively. There was no significant difference (p < 0.05) in the concentrations of the toxic metals amongst the various infant formula based on packaging (metal container, aluminum sachet), types (milk-based, corn-based, soy-based), and classification (beginner, beginner, special, continuation). The infant formula samples which contained detectable levels of Pb, Cd and As had higher concentrations of these metals compared to breast milk and infants have a higher average weekly intake of these metals through infant formula. Findings from this study indicate that infant formula is a source of toxic metal exposure for infants. Highlights: As, Pb and Cd were observed in 59%, 8% and 10% of infant formula brands, respectively. Mean concentrations (±SD) of the metals (in μg/kg) were determined to be 371 ± 581 (Pb), 255 ± 179 (Cd) and 88.7 ± 71 (As). The contamination levels (in μg/kg) of the metals ranged from: 31.0–1040 (Pb), 38.0–476 (Cd) and 12.0–251 (As). There was no significant difference (p < 0.05) in the concentrations of the toxic metals amongst the various infant formula. Samples which contained detectable levels of Pb, Cd and As had higher concentrations compared to breast milk.